Environmental Hazard Assessment of Jarosite Waste Using Batch Leaching Tests - M. Kerolli – Mustafa; L. Ćurković; M. Ujević Bošnjak; T. Rezić (Chemical and Biochemical Engineering Quarterly, 2018)
Jarosite waste samples from Trepça Zinc Industry in Kosovo were subjected to two batch leaching tests as an attempt to characterize the leaching behavior and mobility of minor and major elements of jarosite waste. To achieve this, deionized water and synthetic acidic rain leaching tests were employed. A two-step acidic treatment in microwave digestion system were used to dissolve jarosite waste samples, followed by determination of Al, Ag, As, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, P, Pb, S, Si, Sr, and Zn by inductively coupled plasma optical emission spectrometry (ICP-OES). The validation of the procedure was performed by the analysis of two geochemical reference materials, S JR-3 and S Jsy-1. Two toxicity leaching tests revealed a high metal releasing of Cd, Cu, Ni, Mn, Pb, Zn, and As, and the metal release risk for these elements is still very high due the low pH and acid rain. The statistical analysis showed useful data information on the relationship between elements in jarosite samples in two different extraction conditions (deionized water and synthetic acid rain).